2019
DOI: 10.1002/ece3.5053
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the energy expenditure of free‐ranging polar bears using tri‐axial accelerometers: A validation with doubly labeled water

Abstract: Measures of energy expenditure can be used to inform animal conservation and management, but methods for measuring the energy expenditure of free‐ranging animals have a variety of limitations. Advancements in biologging technologies have enabled the use of dynamic body acceleration derived from accelerometers as a proxy for energy expenditure. Although dynamic body acceleration has been shown to strongly correlate with oxygen consumption in captive animals, it has been validated in only a few studies on free‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 88 publications
3
47
0
Order By: Relevance
“…S3). This is consistent with previous studies in the same region (Mauritzen et al 2001, 2002, Hamilton et al 2017, Tartu et al 2018 and other regions (Stirling & Parkinson 2006, Pagano & Williams 2019. There were large interindividual variations within ecotypes suggesting that individual polar bears differ in their habitat use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S3). This is consistent with previous studies in the same region (Mauritzen et al 2001, 2002, Hamilton et al 2017, Tartu et al 2018 and other regions (Stirling & Parkinson 2006, Pagano & Williams 2019. There were large interindividual variations within ecotypes suggesting that individual polar bears differ in their habitat use.…”
Section: Discussionsupporting
confidence: 92%
“…Polar bears with different spatial strategies have different energy requirements (Mauritzen et al 2001, Pagano & Williams 2019, Blévin et al 2020. Studies on the Southern Beaufort Sea and Chukchi Sea populations suggest that energy requirements are tightly related to movement patterns (Ware et al 2017, Pagano et al 2018, and it has been recently shown that spatial strategy influences energy requirements for polar bears of the Barents Sea population (Blévin et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of doubly labelled water (DLW) remains one of the best techniques for estimating metabolic rates under natural conditions (Nagy et al , 1999; Shaffer, 2011), but it can be infeasible for many species because it typically requires an animal to be captured twice within a period of days to weeks (Speakman, 1997). Metabolic rates of captive animals are thus increasingly used to fill the metabolic data gap and are particularly useful for the ability to isolate the costs of discrete activities and physiological or life history events that can then be applied to estimate the energy requirements of wild populations (Williams et al , 2007; Thometz et al , 2014; Pagano and Williams, 2019). Captive studies cannot, however, mimic the complex behaviour exhibited by free-ranging animals.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated ODBA as the absolute sum of dynamic acceleration across the three axes (Wilson et al ). For swimming movements, we used the mean swimming metabolic rate determined by Griffen () (2.75 mL O 2 ·g ‐1 ·h ‐1 ) as described by Pagano and Williams (). To evaluate potential differences in energy expenditure between bears that moved to land and those that stayed on the sea ice, we used two‐sample t ‐tests in R, which are considered to retain suitable statistical power at low sample sizes (de Winter ).…”
Section: Methodsmentioning
confidence: 99%